Vitamin P₂ : new perspectives in painting - Hasting, Julia; Schwabsky, Barry (London : Phaidon, 2011)
This edition includes 115 artists from over thirty countries who represent the best of the new international painting.
Artists include: Nina Chanel Abney, Richard Aldrich, Ellen Altfest, Hurvin Anderson, Karin Mamma Andersson, Juan Araujo, Tauba Auerbach, Jules De Balincourt, Antonio Ballester Moreno, Hernan Bas, Tilo Baumgärtel, Michaël Borremans, Mark Bradford, Kerstin Brätsch, Lisa Brice, Rafał Bujnowski, Stephen Bush, Varda Caivano, Brian Calvin, Gillian Carnegie, Sarah Crowner, William Daniels, Noah Davis, Philippe Decrauzat, Benjamin Degen, Kaye Donachie, Pierre Dorion, Milena Dragicevic, Thomas Eggerer, Nicole Eisenman, Ida Ekblad, Michael Fullerton, Adrian Ghenie, Wayne Gonzales, Mark Grotjahn, Wade Guyton, Josephine Halvorson, N.S. Harsha, Richard Hawkins, Carmen Herrera, Alex Hubbard, Jacqueline Humphries, Nathan Hylden, Merlin James, Xylor Jane, Jia Aili, Magdalena Jitrik, Chantal Joffe, Chris Johanson, Jitish Kallat, Maki Na Kamura, Jacob Kassay, Khalif Kelly, Martin Kobe, Jutta Koether, Tomasz Kowalski, Makiko Kudo, Stefan Kürten, Li Dafang, Li Shurui, Li Songsong, Liang Yuanwei, Liu Xiaodong, Marcin Maciejowski, Tala Madani, Nalini Malani, Victor Man, I Nyoman Masriadi, Birgit Megerle, Dianna Molzan, Katy Moran, Kristine Moran, Justin Mortimer, Farhad Moshiri, Surendran Nair, Odili Donald Odita, Paulina Olowska, Christopher Orr, Silke Otto-Knapp, Alessandro Pessoli, Jon Pestoni, Johannes Phokela, Vitaly Pushnitsky, R. H. Quaytman, Blake Rayne, Clare Rojas, Sterling Ruby, Christopher Ruckhäberle, Serban Savu, Maaike Schoorel, Dana Schutz, Raqib Shaw, Amy Sillman, Anj Smith, Josh Smith, Glenn Sorensen, Neal Tait, Mickalene Thomas, Padraig Timoney, Alexander Tinei, Phoebe Unwin, Lesley Vance, Pieter Vermeersch, Charline Von Heyl, Kelley Walker, Wang Xingwei, Corinne Wasmuht, Matthias Weischer, Andro Wekua, Wendy White, Katharina Wulff, Lynette Yiadom-Boakye, Luiz Zerbini, Zhang Enli, Jakub Julian Ziolkowsi.
Includes essay Everyday painting / by Barry Schwabsky.
Includes bibliographical references and index.
boek